Levodopa Versus Dopamine Agonist after Subthalamic Stimulation in Parkinson's Disease. Issue 3 (9th November 2020) - Picillo, Marina; Phokaewvarangkul, Onanong; Poon, Yu‐Yan; McIntyre, Cameron C.; Beylergil, Sinem Balta; Munhoz, Renato P.; Kalia, Suneil K.; Hodaie, Mojgan; Lozano, Andres M.; Fasano, Alfonso
Abstract: Background: No clinical trials have been specifically designed to compare medical treatments after surgery in Parkinson's disease (PD). Objective: Study's objective was to compare the efficacy and safety of levodopa versus dopamine agonist monotherapy after deep brain stimulation (DBS) in PD. Methods: Thirty‐five surgical candidates were randomly assigned to receive postoperative monotherapy with either levodopa or dopamine agonist in a randomized, single‐blind study. All patients were reevaluated in short‐ (3 months), mid‐ (6 months), and long‐term (2.5 years) follow‐up after surgery. The primary outcome measure was the change in the Non‐Motor Symptoms Scale (NMSS) 3 months after surgery. Secondary outcome measures were the percentage of patients maintaining monotherapy, change in motor symptoms, and specific non‐motor symptoms (NMS). Analysis was performed primarily in the intention‐to‐treat population. Results: Randomization did not significantly affect the primary outcome (difference in NMSS between treatment groups was 4.88 [95% confidence interval: −11.78–21.53, P = 0.566]). In short‐ and mid‐term follow‐up, monotherapy was safe and feasible in more than half of patients (60% in short‐ and 51.5% in mid‐term follow‐up), but it was more often possible for patients on levodopa. The ability to maintain dopamine agonist monotherapy was related to optimal contact location. In the long term, levodopa monotherapy was feasible only in a minority of patients (34.2%), whereas dopamine agonist monotherapy was not tolerated due to worsening of motor conditions or occurrence of impulse control disorders. Conclusions: This trial provides evidence for simplifying pharmacological treatment after functional neurosurgery for PD. The reduction in dopamine receptor agonists should be attempted while monitoring for occurrence of NMSs, such as apathy and sleep disturbances. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society